TRAUMA AND SELF-DISCOVERY IN SADE ADENIRAN’S IMAGINE THIS - IYANUOLUWA TAIWO AKINLUYI (International Studies Journal, 2025)
This paper examines the multifaceted journey of the protagonist as she navigates through layers of psychological trauma and embarks on a transformative quest for self-understanding in Sade Adeniran’s Imagine This. Existing studies have focused on inter-cultural conflicts, existentialism, psycho-pathology, racism, and victimization but have not adequately studied the causes of psychological trauma, self-discovery and emancipation from the trauma as portrayed in the text. This study, therefore, examines the effect of psychological trauma on the victim as a result of her inner mental process and gains insight into the unconscious intention of the character. This is an attempt to show how psychoanalysis can be used to understand the behaviour of characters and what inspires the action in them. Analytical research method is employed in this study. Sigmund Freud’s Psychoanalytical Theory and Cathy Caruth’s Trauma Theory is used in the course of the analysis. The paper reveals the psychological trauma and finds the strategies of self-discovery. Adeniran’s Imagine This also examines the psychological effects of broken marriage, parental irresponsibility, hostility, alienation and defective ‘personality’ structure on a child at formative age. Lola, a teenage girl recounts the pains of harsh realities of cultural shock occasioned by her sudden change of environment which inflicts on her psyche deep sense of neglect, deprivation and abandonment.  The study concludes by portraying the effect of trauma and the emancipation from such trauma. This paper discovers that characters have some psychological trauma; this arises from painful psychological experiences in their lives. Some were subjugated to oppression, inferiority complex and depression.